CONSTITUTIONALIZATION OF THE LEGAL SYSTEM OF UKRAINE: CURRENT PROBLEMS - MARTSELIAK, O.; STRELTSOVA, O. (Ehrlich's Journal, 2023)
The article deals with theoretical and practical aspects of constitutionalization of the legal system of Ukraine. It can be stated that ambiguity in the use of the term “constitutionalization” and identifying this concept with a number of others. For a better understanding of its nature the concept of “constitutionalization” shall be explored within the paradigm of constitutionalism, through relationship with the categories of “constitutionalism” and “constitution”. However, constitutionalization in Ukraine of state and public life there must be the implementation of constitutional provisions, when the provisions of the Constitution are causative factor in the state and contribute to the formation of a qualitatively new constitutional-legal norms, relations, institutions.